Evaluating the viability of ciphertext-policy attribute-based encryption on service-oriented health information exchange systems - Felizmenio, Edgardo P. Jr
Interoperability in Healthcare stands for the sharing of data among systems for providing healthcare, and it has been shown that achieving interoperability leads to several benefits that affect consumers and other stakeholders. With this, several countries have already implemented a Health Information Exchange (HIE) to enable interoperability in their areas. However, certain regions, third-world countries in particular, may find several challenges in implementing HIEs given the technology and resources that are currently available. OpenHIE is an initiative that aims to address the interoperability challenges in underserved regions. OpenHIE provides a framework for implementing an HIE which is based on the Service-Oriented Architecture (SOA). Its design has been proven to work in Rwanda, and other countries and organizations have shown interest in adopting its components. In its current implementation, OpenHIE can provide the de facto standard for securing health information systems. However, several essential security features have yet to be implemented, namely fine grained access control, security levels and clearances, and consent management. In this study, we explore the application of Ciphertext-Policy Attribute Based Encryption (CP-ABE) on OpenHIE to realize the aforementioned security features. In CP-ABE, stored data is encrypted with a certain policy and encryption keys are embedded with attributes. In order to decrypt records for consumption, the attributes in the encryption key must satisfy the policy in the ciphertext. Other operations such as modifying existing records and providing consent may require the reencryption of data and the re-issuance of keys. For implementation, we used the CP-ABE of Bethencourt, et. al, [6] through the Charm framework [4]. It is evident that applying CP-ABE will affect how the operations in the HIE must be implemented. In addition to implementing operations, the performance of the HIEs on 1-10 attributes is also measured to assess its viability. Different configurations of the HIE are tested: one without CP-ABE (default), one with CP-ABE inside the HIE (ABE-IN), and one with CP-ABE outside (ABE-OUT). Results show that for only one user, the default HIE has higher transactions per second than ABE-IN and ABE OUT. However, as the number of users increase, the ABE-OUT HIE serves more transactions per second. We will also see that ABE-IN and ABE-OUT consumes more space in the Shared Health Record, especially when the number of attributes increase. However, in the interoperability layer, the ABE-OUT HIE consumes more space than the default HIE due to the way they are programmed. An analysis of the TCP connections in the HIE also shows that for a single-threaded setup, the bandwidth is not much utilized as the number of users increase.